2021
DOI: 10.1002/adsu.202100184
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Tuning of Covalent Triazine Framework Nanoshells for Highly Efficient Photocatalytic H2O2 Production

Abstract: and sustainable production technologies is highly urgent. Among many potential options, semiconductor-based photocatalytic H 2 O 2 synthesis from two-electron oxygen reduction at ambient conditions offers a promising strategy, which only uses clean and sustainable solar energy as the energy input. [8][9] The challenge is to explore advanced semiconductor photocatalysts with efficient charge-separation efficiency and favorable surface properties in order to shift the reaction pathway toward the desired H 2 O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…17,18 The observed effects might be negligible in very dilute solutions of benzyl alcohol, but they might represent a dominant mechanism under solvent-free (only benzyl alcohol) or biphasic (e.g., equivolumetric benzyl alcohol/water mixtures) conditions. [38][39][40][41][42][43] Two further points are noteworthy with respect to the visible light activity. Firstly, the designation of a 420 nm cut-off filter implies, per definitionem, that the transmittance at 420 nm is 50%, i.e., there can be a small portion of higher energy light still transmitted when using these filters.…”
Section: Does Benzaldehyde Once Formed Undergo Further Transformation...mentioning
confidence: 98%
“…17,18 The observed effects might be negligible in very dilute solutions of benzyl alcohol, but they might represent a dominant mechanism under solvent-free (only benzyl alcohol) or biphasic (e.g., equivolumetric benzyl alcohol/water mixtures) conditions. [38][39][40][41][42][43] Two further points are noteworthy with respect to the visible light activity. Firstly, the designation of a 420 nm cut-off filter implies, per definitionem, that the transmittance at 420 nm is 50%, i.e., there can be a small portion of higher energy light still transmitted when using these filters.…”
Section: Does Benzaldehyde Once Formed Undergo Further Transformation...mentioning
confidence: 98%
“…Photocatalysis is a green and sustainable method to produce H2O2 since it is powered by inexhaustible sunlight 18 . Moreover, it also reduces our energy reliance on unsustainable fossil fuels and alleviates environmental pollution 15,19,20 .…”
mentioning
confidence: 99%
“…In 2014, Shiraishi et al reported that the graphitic carbon nitride ( g -C 3 N 4 ), a metal-free polymer semiconductor, can produce H 2 O 2 under photoirradiation using alcohol and molecular O 2 as the proton and oxygen sources, respectively . Inspired by this seminal work, numerous organic polymer-based photocatalysts have emerged in recent years for photocatalytic production of H 2 O 2 , including g -C 3 N 4 derivatives, conjugated microporous polymers (CMPs), , covalent triazine frameworks (CTFs), , covalent organic frameworks (COFs), linear conjugated polymers (LCPs), , and resorcinol-formaldehyde (RFs) resins. Compared to their inorganic counterparts, these polymeric or “soft” materials are comprised of naturally abundant elements such as C, H, and N. Moreover, recent observation of long-lived charges in organic heterojunctions without electron/hole scavengers suggests that organic polymers are promising for driving kinetically challenging and technologically desirable redox reactions . Thus, they are up-and-coming candidates as low cost and easily processable materials for solar-driven H 2 O 2 production. …”
Section: Emergence Of Polymer Photocatalysts For Solar-driven Hydroge...mentioning
confidence: 99%